(untitled) (Fiep Bulletin - online, 2011)
This study aimed to evaluate the physical workload of employees in a foundry by ergonomic analysis and heart rate variation. It was observed that the activities in the foundry sector, ostemomuscular great burden in the spine and upper limbs due to static postures and repetition of movements. The cargo exceeds human capabilities and limitations, necessitating the need for design changes of this production system, setting the ceiling for manual handling. Through the values of heart rate achieved by the employees evaluated in all the activities the value exceeds the physical capacity.